2021
DOI: 10.1186/s13052-021-01093-6
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of congenital anomalies among newborns in Arsi zone public hospitals, Southeast Ethiopia: a case-control study

Abstract: Background Congenital anomaly is a partial or complete structural and/or functional defect during intrauterine life. Globally, major congenital anomalies account for 6% of all newborns among which about 94% of cases occurred in developing countries. In spite of its public health importance, very limited studies are reported in Ethiopia, and hardly any study in Arsi Zone. Objectives To determine the predictors of congenital anomalies among newborns … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(35 citation statements)
references
References 25 publications
2
28
0
Order By: Relevance
“…Several studies have shown that folic acid reduces occurrence of different forms of congenital anomalies including neural tube defects, orofacial clefts, limb reduction defects, congenital heart defects, as well as abdominal wall defects( 4 , 15 , 16 ). In our study as well, there was a significant association between congenital anomalies and lack of folate supplementation during pregnancy, similar to findings of other studies( 4 , 13 ). This is one of the signals indicating the need to improve the quality of ANC provided at health facilities in those pregnant mothers attending ANC.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Several studies have shown that folic acid reduces occurrence of different forms of congenital anomalies including neural tube defects, orofacial clefts, limb reduction defects, congenital heart defects, as well as abdominal wall defects( 4 , 15 , 16 ). In our study as well, there was a significant association between congenital anomalies and lack of folate supplementation during pregnancy, similar to findings of other studies( 4 , 13 ). This is one of the signals indicating the need to improve the quality of ANC provided at health facilities in those pregnant mothers attending ANC.…”
Section: Discussionsupporting
confidence: 93%
“…Few studies done in Ethiopia have demonstrated that anomalies of the nervous system account for the large proportion( 10 14 ) followed by orofascial( 12 ), musculoskeletal( 11 , 12 ) and gastrointestinal( 10 ) anomalies. Factors associated with congenital anomalies in Ethiopia were exposure to pesticides( 11 , 13 ), consumption of khat( 11 , 13 ), alcohol intake( 13 ), maternal illnesses( 13 ) and lack of folic acid supplementation during current pregnancy( 13 ). The aims of this study are determining the magnitude and types of congenital anomalies and associated factors among neonates admitted to the neonatology ward.…”
Section: Introductionmentioning
confidence: 99%
“…Maternal khat chewing is an independent predictor of congenital anomalies [40 ].This is in line with the ndings of a case-control study conducted in Southeast Ethiopia [22,23]. In our study setting, khat chewing was the most common and popular social practice that most people, including pregnant women, participated in.…”
Section: Discussionsupporting
confidence: 87%
“…According to this study, maternal alcohol consumption during early pregnancy is linked to an increased risk of congenital anomalies [36]. Studies in China [37,38,39], California[36], and Ethiopia [8,22]. This could be because of the complex and wellordered nature of alcohol on developmental processes, which may disrupt fetal development by altering the stem-cell genome via an endogenous and alcohol-derived source of DNA damage, which promotes their degeneration, whereas incorrect repair of this damage results in malignancies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation